2018
DOI: 10.1177/1359457518799076
|View full text |Cite
|
Sign up to set email alerts
|

The invisible handshake: A context for improvisation in music therapy

Abstract: Improvisation is a fundamental aspect of music therapy practice but until recently was much neglected by researchers. This article outlines hitherto unpublished findings from doctorate research completed in 2001, at a time when few investigations were being undertaken. The findings stand the test of time and are detailed in the article as well as updated within the current literature context. The strength of the research is in consideration of underlying temporal, relational aspects of improvisation, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These interactive exchanges via CFMI potentially transform oneself and others by equaling the unequal conversations among diverse musicians. These findings align with research that revealed CFMI’s potential to develop communication skills (Kanellopoulos, 2007; Sutton, 2001; Thomson, 2008), social relationships (Sansom, 2007), and mutual understanding (Canonne & Aucouturier, 2016; Pras et al, 2017), and to propel self-transformation and discovery (Burnard, 2002; Burrows, 2004; Kanellopoulos, 1999). These learnings are foregrounded as a result of CFMI’s socio-communicative nature.…”
Section: Value Of Cfmisupporting
confidence: 84%
“…These interactive exchanges via CFMI potentially transform oneself and others by equaling the unequal conversations among diverse musicians. These findings align with research that revealed CFMI’s potential to develop communication skills (Kanellopoulos, 2007; Sutton, 2001; Thomson, 2008), social relationships (Sansom, 2007), and mutual understanding (Canonne & Aucouturier, 2016; Pras et al, 2017), and to propel self-transformation and discovery (Burnard, 2002; Burrows, 2004; Kanellopoulos, 1999). These learnings are foregrounded as a result of CFMI’s socio-communicative nature.…”
Section: Value Of Cfmisupporting
confidence: 84%
“…This article focuses on my doctoral research conducted in 2001 (Sutton, 2001); the central question was, is improvisation like conversation? To investigate this analogy, 10 free musical improvisations by established, well-known musicians were examined, 1 comprising a cross-section of experienced free improvisers whose music spanned several decades.…”
Section: Research By Analogymentioning
confidence: 99%
“…Due to the predominantly socio-communicative nature of collective free music improvisation (CFMI), performers develop their social relationships and identity as they construct music and its meanings through socio-musical interactions (Burrows, 2004; Sansom, 2007). These interactions develop communicative skills as players converse with fellow improvisers through music, an endeavor paralleling verbal dialoging (Sutton, 2001). Through CFMI, players may converse with different musical genres and skills and engage in reflexive exchanges, which mediates unequal conversations between diverse improvisers (Lange, 2011).…”
Section: Value Of Collective Free Music Improvisation In Music Educationmentioning
confidence: 99%